Climate Protection in the Transport Sector: Climate-Oriented and Socially Fairer Market Design Necessary - Peter Kasten (Wirtschaftsdienst)
Abstract The transport sector in Germany is far from achieving the GHG emission reduction targets set in the Climate Protection Act and, following the revision of the Effort Sharing Regulation, also by the EU. GHG emissions from the transport sector must be cut by almost half of the 2019 level by 2030. The key to achieving this target is a rapid transition to the use of zero-emission vehicles, which have significant advantages over climate-friendly fuels such as e-fuels in terms of cost and speed of emissions reduction. The coalition agreement meets the challenge in the transport sector by setting high targets, but references to policy design are almost completely missing.